Lucanthone and its derivative hycanthone inhibit apurinic endonuclease-1 (APE1) by direct protein binding. - Mamta D Naidu; Rakhi Agarwal; Louis A Pena; Luis Cunha; Mihaly Mezei; Min Shen; David M Wilson; Yuan Liu; Zina Sanchez; Pankaj Chaudhary; Samuel H Wilson; Michael J Waring (PLoS ONE)
Lucanthone and hycanthone are thioxanthenone DNA intercalators used in the 1980s as antitumor agents. Lucanthone is in Phase I clinical trial, whereas hycanthone was pulled out of Phase II trials. Their potential mechanism of action includes DNA intercalation, inhibition of nucleic acid biosyntheses, and inhibition of enzymes like topoisomerases and the dual function base excision repair enzyme apurinic endonuclease 1 (APE1). Lucanthone inhibits the endonuclease activity of APE1, without affecting its redox activity. Our goal was to decipher the precise mechanism of APE1 inhibition as a prerequisite towards development of improved therapeutics that can counteract higher APE1 activity often seen in tumors. The IC(50) values for inhibition of APE1 incision of depurinated plasmid DNA by lucanthone and hycanthone were 5 µM and 80 nM, respectively. The K(D) values (affinity constants) for APE1, as determined by BIACORE binding studies, were 89 nM for lucanthone/10 nM for hycanthone. APE1 structures reveal a hydrophobic pocket where hydrophobic small molecules like thioxanthenones can bind, and our modeling studies confirmed such docking. Circular dichroism spectra uncovered change in the helical structure of APE1 in the presence of lucanthone/hycanthone, and notably, this effect was decreased (Phe266Ala or Phe266Cys or Trp280Leu) or abolished (Phe266Ala/Trp280Ala) when hydrophobic site mutants were employed. Reduced inhibition by lucanthone of the diminished endonuclease activity of hydrophobic mutant proteins (as compared to wild type APE1) supports that binding of lucanthone to the hydrophobic pocket dictates APE1 inhibition. The DNA binding capacity of APE1 was marginally inhibited by lucanthone, and not at all by hycanthone, supporting our hypothesis that thioxanthenones inhibit APE1, predominantly, by direct interaction. Finally, lucanthone-induced degradation was drastically reduced in the presence of short and long lived free radical scavengers, e.g., TRIS and DMSO, suggesting that the mechanism of APE1 breakdown may involve free radical-induced peptide bond cleavage.